Assessment Of Quality of Life in Diabetic Patients with Diabetic Foot Ulcers (DFU) and Without Foot Ulcers: A Cross Sectional Study - Fatima, Dr Afreen; Riaz, Dr Bushra; Anjum, Dr Sayeeda; Imran, Dr Mohd Rasheeduddin; Islam, Dr Mohammed Nazrul (Migration Letters, 2024)
One significant risk factor for long-term, chronic diabetes mellitus is impaired blood glucose levels which contribute to the development of diabetic complications such as diabetic neuropathy, nephropathy and retinopathy. The utmost frequent and notable complication among these is the pathogenesis of diabetic foot ulcer due to prolonged diabetic neuropathy, critically impacting the well-being of patients suffering from it. This study evaluated and compared the quality of life between people with diabetic foot ulcers and those without them. A cross sectional study was conducted using SF 36 questionnaire consisting of questions related to quality of life in seven domains. This questionnaire was distributed to all diabetic patients admitted to surgery department, at Victoria Hospital, Bengaluru. Socio demographic and clinical characteristics of the patients like age of patients, duration of diabetes, treatment taken, presence or absence of autonomic neuropathy also obtained. The analysis comprised a total of one hundred patients. Of these 59 patients had foot ulcer and 41 were without foot ulcer. The answered questionnaire was analyzed using descriptive statistics and it showed low scores in all seven domains of SF-36 questionnaire. Low scores in all seven questionnaire domains, with physical health and pain being the most affected, show that diabetes individuals with foot ulcers have significantly lower health-related quality of life metrics than those without foot ulcers.